Live, virtual, and spectral: being present at the prison (tour)*. Issue 2 (3rd April 2019) - McCann, Bryan J.
ABSTRACT: Drawing on several years of bringing students on a tour of a maximum security prison, I posit the prison (tour) as a live performance that is only legible through distinct but interlocking registers of presence. I argue that the prison (tour) positions and assembles recalcitrant bodies conditioned by live, virtual, and spectral encounters with each other. The convergence of present and absent bodies at the site of the prison and the intermingling of these three registers reveal that while the prison (tour) may function primarily as an embodied performance of discipline, it unravels in salient ways and the participants therein find meaningful, if often subtle, ways of exploiting the resulting ruptures.